Statistical match reports of the 2022 volleyball World Championship in the context of network analysis with Gephi - Sergii Iermakov; Tetiana Yermakova; Krzysztof Wnorowski (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Modern volleyball teams participating in tournaments provide extensive statistical data about their actions. These data are available for analysis and represent a valuable source for assessing the potential and future success of both individual athletes and teams as a whole. In this context, tools such as Gephi become particularly valuable for visualizing and analyzing events at high-level tournaments. Our study aims to create and analyze network models of interaction among men's volleyball teams during the qualifying matches of the 2022 World Championship using the Gephi software.